Abstraction of silver from spent solutions of silvering electrolytes - V. N. Jaglov; G. A. Burak; E. A. Evseeva; A. A. Mezhentsev; I. B. Provorova (Литьë и металлургия, 2003)
There are given the results of study of the process of silver extraction out of silvering electrolyte by means of metal-exchange. There is shown the dependence of silver extraction out of liquors of different concentration on the type and quantity of cementator and process duration. There is determined, that the perspective cementator is TsAM, allowing to extract silver out of liquors fully.